2015
DOI: 10.1016/j.chemphys.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Water rotation barriers on protein molecular surfaces

Abstract: The experimental characterization of hindered-rotation barriers and mapping the energetic heterogeneity of water molecules bound to the molecular "surface" of proteins is critical for understanding the functional interaction of proteins with their environment. Here, we show how to achieve this goal by an original wide-line NMR procedure, which is based on the spectral motional narrowing phenomenon following the melting (thawing) process of interfacial ice. The procedure highlights the differences between globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(82 citation statements)
references
References 34 publications
3
79
0
Order By: Relevance
“…The strategic objective of our work is the thermodynamic characterization of protein molecules beyond their architectural, static description. The attributes introduced in works, moreover, the experimental results reported in Ref. and complemented here, are made use of in the thermodynamic characterization of the studied proteins.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The strategic objective of our work is the thermodynamic characterization of protein molecules beyond their architectural, static description. The attributes introduced in works, moreover, the experimental results reported in Ref. and complemented here, are made use of in the thermodynamic characterization of the studied proteins.…”
Section: Introductionmentioning
confidence: 93%
“…Weak binding was confirmed between Tβ 4 and stabilin CTD and it was suggested that the proteins become slightly more disordered in the complex . Considerable progress has been achieved in several questions of the interpretation of wide line NMR results since relevant references were published . It was realized that the hydrogen nuclei in the water molecules with connection to the proteins act as magnetic probes which are integral parts of the material under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, it delineates the bounded water's movements, reveals the monomeric and oligomeric protein states and also identifies the amyloid molecules in pathological processes. Although, the Aβ 42 fibril and the other disordered/ordered proteins are thermodynamically different, as only the amyloid protein is stable, this versatile NMR-method is also applicable for amyloids (41). Gáspári and Perczel (42) published an interesting and important review of a highly advanced NMR theory/ technique, in a book chapter.…”
Section: Expert Opinion and Outlookmentioning
confidence: 99%
“…Based on this phenomenon a sophisticated wide-line NMR procedure was developed by the Tompa's team with several purposes (41). Among others, it delineates the bounded water's movements, reveals the monomeric and oligomeric protein states and also identifies the amyloid molecules in pathological processes.…”
Section: Expert Opinion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation